(NkOLI^ESTWENNAQ TEORIQ GEOKRIOLOGI^ESKOGO PROGNOZA (B/s - d; (NkRASS(B, (NmAKSIM sEMENOWI^s; (NgUSEWA(B, (NeLENA wQ^ESLAWOWNAs; (NgEWORKQN(B, (NsERGEJ gEORGIEWI^s ((NmOSKWA (B:s (Nmgu(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 254-266 (313 (NNAZW(B.)s
Keywords: (NgEOLOGIQs